Automatic gate sensors - Mohammad Khaled, Muhd Nur Danish Ikhwan; Abdul Rahim, Ruzairi; Sahlan, Shafishuhaza; Ahmad, Nasarudin; Mohamad, Elmy Johana; Mohd. Zain, Rasif; Wahid, Herman; Ahmad, Anita (Penerbit UTHM, 2022)
Advancement in technology is a live of example of this concept. As it is too difficult for a common man to think earlier that can a gate could be opened automatically without any manual work. Also the types included in this system are vast in market. So the technological advancement is required to combine all such features in a single system. Also the system should be easily operatable by any beginner or any incoherent person. It also provides security as it’s the major requirement from any gate by any user, without security the system is of no use. So, security is also a non-comprisable feature of this system. One more problem related to gate is that the user should be reliable on others also the security feature can be compromised due to innumerable reasons that occur related to humans. First gate introduced was completely manual and humans were completely required to open such gates. Then came the next system used on toll booths that opened the gate after the click of the operator over switch. Later came the system that only recognized any type of moving vehicle and then opened the gate using the system, IR detector was used in this type of system. The next system used in the type was the system that only allowed the authorized user the access and opened the gate required to be opened for the unauthorized user. The main task of this system is to reduce manual work and bring technological advancement in the society. At last the system with some modifications from the above system was introduced like opening of gate by mobile application rather than opening it manually. This helps in reducing maximum of the physical work. The cost expenditure on machine is one time which is bearable whereas the cost expenditure on human is recurring and increases with time.